(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical and paraclinical symptoms of snoring patients who underwent surgery at the National Otorhinolaryngology Hospital. Subjects and methods: The research involved 34 patients who sought surgical intervention for snoring at the National Otorhinolaryngology Hospital from January 2024 to September 2024. Results: Among the patient characteristics, the majority are men of working age (38.65 ± 11.44), have few comorbidities (diabetes 2.9%, hypertension 11.7%), and have a very low percentage of obese patients (2.9%). However, the AHI index is severe for the majority (80%). Sleepiness (61.7%) and diminished concentration (41.2%) are the primary symptoms during the day. The most common nighttime symptoms are apnea (82.3%) and loud snoring (100%). When the patient is awake, endoscopic examination rarely reveals the disease’s distinctive symptoms. Turbinate hypertrophy was seen in only 20.6% of cases, 13.5% had hypertrophied uvulae, 14.7% had septal deviation, and 17.6% had large and wide uvulae 13.5% had hypertrophied tonsils at the base of the tongue, and 1 patient (2.9%) had signs of grade 4 tonsil hypertrophy and Mallampati. Conclusions: The study provides a basis for diagnosing snoring/sleep apnea syndrome and planning appropriate treatment, contributing to improving the quality of treatment.